Pengaruh Inovasi Pendidikan terhadap Generasi Millenial - Aminuddin Aminuddin (Unit Pelaksana Teknis Penelitian dan Pengabdian pada Masyarakat (UPT-P4M) STAI Auliaurrasyidin Tembilahan, 2021)
The millennial generation has several characteristics, millennials don't believe in one-way information, prefer cellphones over TV, must have social media, a place for self-actualization and expression, don't like reading conventionally, know more about technology, tend to be disloyal, do a lot of interactive interactions. cashless. Teachers in the millennial era are heavier than the previous era, in addition to understanding aspects of scientific material in teaching, teachers must master technology and become creative and innovative teachers and become role models for millennial generation students. Innovation is a renewal in education both regarding ideas, practices, methods or objects and is qualitatively different from the things that existed before and is deliberately attempted to improve the ability to achieve educational goals and solve educational problems. This study uses a literature study method, collecting primary and secondary sources related to the object of this research the influence of educational innovation on the millennial generation.